Modifikasi Limbah Abu Layang menjadi Adsorben untuk Mengurangi Limbah Zat Warna pada Industri Tekstil - Sutrisno, Bachrun; Hidayat, Arif; Mufrodi, Zahrul (Universitas Ahmad Dahlan, 2014)
Abundant supplies of coal make this compound as alternative fuels, especially for the industry. However, using of coal has shortcomings; incomplete combustion of coal produces solid waste that often called the fly ash. Results of mineral analysis showed that fly ash contain metal oxides such as silica (SiO2), alumina (Al2O3) and iron (Fe2O3). The presence of silica and alumina components allows fly ash to be synthesized into materials that have structure similar to zeolite. This material is known as zeolite like materials (ZLM).This study aims to synthesize ZLM of fly ash as adsorbent material. To determine the successful of synthesis also has been analyzed physicochemical properties of zeolite-like material. Then the results are used as adsorbent of textile dyes.The results showed that fly ash can be synthesized into zeolite-like material, this is indicated by the increasing of physicochemical properties. The experiment shown that the adsorption ability of fly ash in the reduction of textile dyes after modifiedis better.